1974
DOI: 10.1111/j.1651-2227.1974.tb04782.x
|View full text |Cite
|
Sign up to set email alerts
|

Fluoride, Mineralisation Defects of the Enamel, and Tooth Width

Abstract: Fluoride, Mineralisation defects of the enamel, and tooth width. Acta Paediat Scand, 63: 188, 1974.-The purpose of the investigation was to appraise the frequency of enamel mineralisation defects in 151 children, aged 8-11 years, born and raised in a district in Vasterbotten county in northern Sweden, where the fluoride content of the drinking water ranges up to 2 mg/l, and to examine the mesiodistal widths of the teeth for effects of fluoride in these concentrations. The control group consisted of 213 childre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

1975
1975
1987
1987

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 10 publications
0
3
0
Order By: Relevance
“…The size of the teeth does not seem to be affected consistently by the F supply during their development [Wallenius, 1959;Lovius and Goose, 1969;Simpson and Castaldi, 1969;Baalack and Frisk, 1969;Grahnen et al, 1974], but there is a report of greater width of the dental arches with a higher F supply [Baalack and Frisk, 1969].…”
Section: Early Developm Ent O F Stu D Ie S On F/caries Relationshipmentioning
confidence: 99%
“…The size of the teeth does not seem to be affected consistently by the F supply during their development [Wallenius, 1959;Lovius and Goose, 1969;Simpson and Castaldi, 1969;Baalack and Frisk, 1969;Grahnen et al, 1974], but there is a report of greater width of the dental arches with a higher F supply [Baalack and Frisk, 1969].…”
Section: Early Developm Ent O F Stu D Ie S On F/caries Relationshipmentioning
confidence: 99%
“…Based on studies of several species, including hu mans, daily fluoride doses of about 0.1 mg/kg during tooth development are suf ficient to cause marginal dental fluorosis [Sum'eet al, 1972;Kruger, 1970;AngmarMansson et al, 1976;Forsman , 1977], It is, however, questionable whether a single value for fluoride intake can reliably pre dict dental fluorosis for all populations. Several studies have reported endemic in volvement in the apparent absence of ex cessive fluoride intake [Leatherwood et al, 1965;Nanda et al, 1974;Grahnen et al, 1974], Further, found developing enamel fluoride levels and the degree of rat incisor fluoro sis to be independent of or inversely relat ed to fluoride intake depending on acidbase status. They suggested that fluoride balance among individuals or populations could vary sufficiently to render intake da ta invalid as predictors of dental fluorosis.…”
mentioning
confidence: 99%
“…It has been shown that increasing dietary levels of fluoride produces correspondingly more marked changes in the morphology ofthe rat molar (12). However, GRAHNEN et al (19), could find no such correlation when comparing the mesio-distal width of teeth in 9-yr-old children from a non-fluoridated area and an area with drinking water fluoride content of 2 mg/1. An optimum-fluoride sample was not included in their study.…”
mentioning
confidence: 97%